1994
DOI: 10.1097/00007890-199404150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sequential Serum Interleukin-6 Levels in Liver Allograft Recipients

Abstract: Control serum levels of IL-6 measured by ELISA in 30 healthy blood donors or volunteers were 18±S4 pg/ml (mean ± SD). Pretransplant serum levels of IL-6 in 169 adult candidates for liver transplantation were significantly higher than control in those with fulminant hepatitis (203±232 pg/ml), alcoholic cirrhosis (116±257 pg/ml), and hepatocellular carcinoma (82±105 pg/ml). With these data as background, plasma or serum levels of EL-6 were monitored in 24 adult patients after first OLT and correlated with the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Interestingly, these 2 inflammatory mediators, which counteract each other, closely reflect ischemia/reperfusion, and this indicates that the inflammatory network functions to balance the detrimental effects of this condition. CXCL8, a chemokine,47 and IL‐6, a proinflammatory cytokine,48 increased with ischemia, but a positive trend was also detected with rejection. This indicates that these mediators are expressed by a general activation of the immune system and not specifically by the adaptive (cell‐mediated) or innate immune system.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, these 2 inflammatory mediators, which counteract each other, closely reflect ischemia/reperfusion, and this indicates that the inflammatory network functions to balance the detrimental effects of this condition. CXCL8, a chemokine,47 and IL‐6, a proinflammatory cytokine,48 increased with ischemia, but a positive trend was also detected with rejection. This indicates that these mediators are expressed by a general activation of the immune system and not specifically by the adaptive (cell‐mediated) or innate immune system.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that IL-6 plays an important role in the regulation of inflammatory and immunological responses (Kishimoto, 1989). Kita et al (1994) and Warlé et al (2003) reported that IL-6 expression was markedly elevated during liver allograft rejection. The present study displayed a close correlation between IL-6 and IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Kita et al . observed in contrast a marked rise of IL‐6 during ACR and during infection, however, the rise pattern was distinguishable between both …”
Section: Acute Cellular Rejectionmentioning
confidence: 76%
“…Kita et al observed in contrast a marked rise of IL-6 during ACR and during infection, however, the rise pattern was distinguishable between both. 23 Interleukin-15 is produced by non-lymphatic cells including macrophages, dendritic cells and epithelial cells. Its biologic activities are similar to those of IL-2.…”
Section: Serum Markers Related To Inflammationmentioning
confidence: 99%